STRATEGY OF THE OFFICE OF COOPERATIVES, SMES, TRADE AND MANPOWER IN EFFORTS TO DEVELOP MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN PASAMAN REGENCY - Esa Febiyani Jezria; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Development is an effort in an effort to increase the potential of the community in order to be able to realize self-sufficiency so as to create sustainable prosperity. The growth of MSME sectors and carrying out development is one of the government's focuses to achieve this economic independence. Micro, Small and Medium Enterprises in the future will act as stabilizers and drivers of economic growth so that they can improve the standard of living and welfare of the nation and state. Therefore, a good development strategy is needed by the Office of Cooperatives, SMEs, Trade and Labor for MSME actors in Pasaman Regency. The purpose of this study is to formulate a MSME development strategy and to find out what factors influence the development carried out by the Office of Cooperatives, SMEs, Trade and Labor. The research method used is a qualitative research method with a descriptive approach. The results of the research show that the development carried out is still not running optimally and has not achieved the expected goals. This is due to the low quality of human resources, facilities and infrastructure to support activities and inadequate market access. The Office of Cooperatives, SMEs, Trade and Manpower found obstacles in determining what strategy to determine according to the factors at hand, but the Office of Cooperatives, SMEs, Trade and Manpower continues to strive to develop SMEs in Pasaman Regency. The advice given is that the Office of Cooperatives, SMEs, Trade and Manpower must be able to take advantage of strengths and opportunities and minimize weaknesses and threats, provide technical and educational training to employees, provide information regarding capital, use social media as promotional activities, and the need for coordination and support from each actor. Keywords: Strategy, Development, UMKM